USE OF BUCCAL PAD OF FAT OROANTRAL FISTULA REPAIR - Tariq Javed; Qurat ul Ain (Journal of University Medical & Dental College, 1970)
ABSTRACT There are many causes of oroantral fistulas but the extraction of a maxillary molar or premolar is most common cause. The other reasons could be trauma, malignant tumors, osteomyelitis, or syphilis1. When the primary fistula repair fails to heal spontaneously during first three weeks of surgery, a secondary repair may be indicated. Many techniques have been advocated for closure of fistulas like Killey & Keys (1969), Tideman et al (1986), and FGYEDI (1977). And some traditional methods of repair include buccal advancement flaps, palatal rotation and palatal transposition flaps, tongue flaps, and naso-labial flaps2. The most common technique is trapdoor technique3. The aim of this report is reporting clinical case of closing oroantral fistula through buccal fat pad.